2020
DOI: 10.1111/1556-4029.14457
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mitragynine in Mitragyna Speciosa (Kratom) Using Surface‐Enhanced Raman Spectroscopy with Handheld Devices

Abstract: A simple, quick, selective, sensitive, and effective field‐friendly method capable of being used by nonexperts has been developed for detecting mitragynine in Mitragyna speciosa (kratom) using surface‐enhanced Raman spectroscopy (SERS). Over 100 samples and blanks (known to be either positive or negative for the presence of mitragynine) were examined in duplicate using five identical handheld Raman spectrometers, which provided a data set of over 1,000 examinations. Based on the results of these analyses, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…Samples were first prepared for SERS analysis by extracting the benzodiazepines in tablets and capsules using 10% MeOH in water diluent followed by addition of Ag colloids and aggregating agent. This method has been successfully demonstrated by our group to be effective in detecting a wide range of analytes [24][25][26]. If suitable results were not achieved for a given sample using this method, the sample was prepared for SERS analysis by separating the benzodiazepine of interest from tablet or capsule using 10% ammoniated chloroform followed by addition of 1 N HCl and Au colloids.…”
Section: Methods Development Performance Metricsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples were first prepared for SERS analysis by extracting the benzodiazepines in tablets and capsules using 10% MeOH in water diluent followed by addition of Ag colloids and aggregating agent. This method has been successfully demonstrated by our group to be effective in detecting a wide range of analytes [24][25][26]. If suitable results were not achieved for a given sample using this method, the sample was prepared for SERS analysis by separating the benzodiazepine of interest from tablet or capsule using 10% ammoniated chloroform followed by addition of 1 N HCl and Au colloids.…”
Section: Methods Development Performance Metricsmentioning
confidence: 99%
“…Additionally, all the SERS spectra of the reference standards used Ag colloids solutions with exception of clonazepam, diazepam, and temazepam, which used Au colloids. The SERS signature collection data revealed that APIs in their free base form resulted in better spectral features using Ag colloids and KBr salt [24][25][26] while those in their HCl salt form had enhanced spectral features with Au colloids and LiCl salt [36].…”
Section: Sers Benzodiazepines Signature Spectramentioning
confidence: 99%
See 2 more Smart Citations
“…The FDA plans to foster its enforcement actions by collaborating with Customs and Border Protection (CBP), by increasing the num- [8,9]. This structural information obtained using SERS [10] is used to reliably screen and detect APIs in finished dosage tablets [11], in bodily fluids [12][13][14][15] and in ground plant powder [16]. Additionally, Raman spectrometers have been miniaturized into handheld devices that are rugged, robust, and easily portable, making them ideal for IMFs and ECHs where space is often limited.…”
Section: Introductionmentioning
confidence: 99%